Pendampingan Pembentukan Peraturan Desa Tentang Pencegahan Perkawinan Anak Desa Gelangsar Kecamatan - Karyati, Sri; Ulum, Hafizatul; Damayanti, Gusti Ayu Ratih; Jannah, Miftahul; Arham, Zawil (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: Child marriage is one form of rights that have an impact on various aspects ranging from health, education, economy, psychology, and gender equality. One of the efforts to prevent and handle child marriage is to strengthen laws and policies that protect children. So it is very urgent to provide assistance and facilitation in the formation of village regulations on preventing child marriage in Gelangsar Village.Purposes of Devotion: Increasing the knowledge and capabilities of village government officials, members of the Village Consultative Body, Community Leaders, increasing knowledge and encouraging synergistic performance between village government officials, members of the Village Consultative Body and Community Leaders in producing village regulations that are in accordance with the provisions of laws and regulations. Method of Devotion: The method used is counseling and assistance in the formation of village regulations for the community, especially for the Gelangsar Village Government, Bamusdes and village government officials as well as community leaders of Gelangsar Village.Results of the Devotion: After the implementation of the activity, it was discovered that the Gelangsar village government did not yet have village regulations on preventing child marriage as a form of village effort to prevent the increase in the number of child marriages.